2014
DOI: 10.2527/jas.2013-7102
|View full text |Cite
|
Sign up to set email alerts
|

Influence of trough versus pasture feeding on average daily gain and carcass characteristics in ruminants: A meta-analysis

Abstract: Quantitative meta-analysis was run on 108 publications featuring 116 experiments and 399 treatments dealing with the effect of trough or pasture feeding environment (FE) on ruminant performances. The objective was to compare the effect of trough or pasture FE on ADG, diet OM digestibility (OMD), various carcass characteristics, and the interaction between FE and complementation modalities. Live weight was adjusted to compare results between species. Results showed that trough-fed animals had higher ADG (+17.89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
5
0
1
Order By: Relevance
“…Concentrate intake had a positive effect on ADG per animal or per ha, with a maximum of 3.5 g/kg BW of ADG, consistent with values published by other authors investigating tropical contexts (Leng, 1990;Poppi and McLennan, 1995;Dixon and Egan, 2000). More recently, a meta-analysis including studies comparing feeding in stalls and at pasture (Agastin et al, 2014) showed that CI is related to ADG (slope of 0.13), which is very similar to the slope calculated in the present study from a different set of published data. The concentrate intake effect on DDMI was also measured, and the calculated substitution rate (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…Concentrate intake had a positive effect on ADG per animal or per ha, with a maximum of 3.5 g/kg BW of ADG, consistent with values published by other authors investigating tropical contexts (Leng, 1990;Poppi and McLennan, 1995;Dixon and Egan, 2000). More recently, a meta-analysis including studies comparing feeding in stalls and at pasture (Agastin et al, 2014) showed that CI is related to ADG (slope of 0.13), which is very similar to the slope calculated in the present study from a different set of published data. The concentrate intake effect on DDMI was also measured, and the calculated substitution rate (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…Le fourrage tassé dans les auges ne nécessite alors pas d'effort important de préhensibilité. Au pâturage il n'en est pas de même car le fourrage est dressé et plus épars, affectant alors la quantité et la qualité de la MS prélevée par bouchée (Prache et Peyraud 1997, Agastin et al 2014. Et dans ces conditions l'ingestion n'est pas forcément liée à la digestibilité.…”
Section: / Prévoir La Performance Animale à Partir Des Apports Nutritunclassified
“…Currently no robust viable methods for reducing CH 4 emissions from foraging ruminants exist (Buddle et al 2011). However, research suggests if freeranging cattle are provided a high-quality diet, CH 4 emissions can be reduced (Ricci et al 2014) and pasture-fed ruminants may be able to achieve comparable performance and greater muscle percentage compared with pen-fed ruminants with similar diets (Agastin et al 2014). Therefore, the potential to optimise diet quality of free-ranging cattle by keeping them moving to the highest quality forage on a landscape using VF may offer management that can lower CH 4 emissions from ruminantdominated landscapes worldwide.…”
Section: Management Of Individual Animals and Virtual Fencingmentioning
confidence: 99%